SIFAT KIMIA DAN FISIK TANAH YANG BERPENGARUH TERHADAP PRODUKSI BAWANG DAUN (Allium fistulosum L) SERTA NILAI EKONOMI LAHAN PADA BERBAGAI KETINGGIAN (Studi Kasus di Wilayah Pacet, Cianjur, Jawa barat) - Wulanningtyas, Heppy Suci; Malik, Afrizal (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
This  research  aims  to  (1)  identification  the  effect  of  soil  physical  and chemical characteristics  to the yield of green onion planted from 800  -  1.400 metres above  sea  level  (mdpl),  (2)  identification  of  fertilizer  and  elevation  effect,  (3) identification  of  landrent  with  potential  development.  The  experimental  plots  were located in Pacet, Cianjur Regency, West Java. This research utilize primary data of soil physical and chemical characteristics that is pH, C-Organic, Total N, P, Ca, Mg, K,  Na,  KTK,  KB,  Al,  H,  Fe,  Cu,  Zn,  Mn,  sand,  dust  and  clay  texture.By  employing Forward Stepwise  –  Multiple Regression, it was showed that Fe has a positive effect to  green  onion  production  at  the  non  fertilized  farmland,  while  Na  and  Al  have negative  effects.  Adversely,  at  the  fertilized  farmland,  all  significant  factors  have negative effect, a case in point : elevation, Zn element and sand texture. Fertilization has a positive effect to green onion production at all level of elevation. Non fertilized farmland  could  produce  average  yield  of  onion  production  from  800  -  1.400  mdpl successively as follows : 13.395,1 kg/ha, 17.263,4 kg/ha, 14.351,9 kg/ha and 15.802,5 kg/ha. While fertilized farmland could produce average yield of onion production from 800  -  1.400 mdpl successively as follows : 18.172,8 kg/ha, 23.415,6kg/ha, 20.655,3 kg/ha  and  20.853,9  kg/ha.  Fertilization  can  increase  productivity,  and  the  highest productivity was reached at 1.000 mdpl. The highest landrent reached at 1.400 mdpl. The landrent from 800 -  1.400 mdpl are Rp. 9.151 /m2, Rp. 8.386/m2,Rp.7.337/m2 and Rp. 10.522/m2.